2008
DOI: 10.3171/jns/2008/109/7/0006
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following endoscopic, expanded endonasal resection of suprasellar craniopharyngiomas: a case series

Abstract: Object. Craniopharyngiomas are challenging tumors that most frequently occur in the sellar or suprasellar regions. Microscopic transsphenoidal resections with various extensions and variations have been performed with good results. The addition of the endoscope as well as the further expansion of the standard and extended transsphenoidal approaches has not been well evaluated for the treatment of this pathological entity.Methods. The authors performed a retrospective review of all patients who underwent a pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
234
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 280 publications
(249 citation statements)
references
References 36 publications
(56 reference statements)
4
234
1
7
Order By: Relevance
“…Endonasal endoscopic transsphenoidal resection of craniopharyngiomas, compared with open transcranial approaches, has been shown to result in comparable or even greater rates of extent of resection and GTR. 3,5,11,13,21,24,27 Moreover, rates of visual improvement may in fact be higher. 24 Nevertheless, debate regarding the relative merits of endonasal endoscopic surgery compared with open transcranial approaches continues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endonasal endoscopic transsphenoidal resection of craniopharyngiomas, compared with open transcranial approaches, has been shown to result in comparable or even greater rates of extent of resection and GTR. 3,5,11,13,21,24,27 Moreover, rates of visual improvement may in fact be higher. 24 Nevertheless, debate regarding the relative merits of endonasal endoscopic surgery compared with open transcranial approaches continues.…”
Section: Discussionmentioning
confidence: 99%
“…22,27 An endoscopic transsphenoidal approach offers a more direct route to the tumor, avoiding brain retraction, minimizing manipulation of the optic nerves and adjacent small perforating vessels, and resulting in equally high gross-total resection (GTR) rates compared with transcranial series, as well as potentially better visual results. 3,5,11,13,21,24,27 Although there are increasing data about the oncological, neurological, and hormonal outcomes for this treatment option, there are no studies assessing postoperative QOL. In an effort to gain a better understanding of the impact of an endoscopic approach in the treatment of craniopharyngiomas, we used accepted site-specific QOL metrics to measure postoperative QOL in a series of patients with craniopharyngiomas by using their own preoperative data as an internal control in a subset of patients, as well as data from a separate group who underwent endonasal endoscopic pituitary surgery, to control for the approach and highlight disease-specific morbidity.…”
mentioning
confidence: 99%
“…24 Nonetheless, various case series have demonstrated exceptionally high rates of CSF leak following expanded endonasal approaches despite the incorporation of a vascularized NSF. 17,18 This underscores the importance of utilizing a sound multilayered reconstruction technique. Additionally, alternative methods for closure must be available in the event that a NSF cannot be harvested due to tumor invasion.…”
Section: Discussionmentioning
confidence: 99%
“…16 Many other studies have demonstrated a wide range of CSF leak rates following resection of these lesions, as well, ranging from 9.5 to 58% with a variety of multilayered closure methods. 2,[17][18][19][20][21] Previously, autologous free grafts including fat, muscle, fascia lata, and nasal septal bone/cartilage have served as viable options for skull base reconstruction following endoscopic endonasal surgery. Kaptain et al encountered a 2.3% postoperative CSF leak rate among 257 patients with intrasellar pathologies who were reconstructed with autologous tissues after endoscopic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Gardner et al [ 47 ] utilized an endonasal endoscopic approach for 16 patients with craniopharyngiomas of the suprasellar region. Of 11 patients in whom complete resection was planned, near-total resection ( > 95%) or GTR was achieved in 91% (10/11); 13/14 (93%) patients had some degree of visual improvement and no patient had visual worsening.…”
Section: Craniopharyngiomasmentioning
confidence: 99%